First report of Amynthas carnosus (Goto & Hatai, 1899) (Oligochaeta: Megascolecidae) in the Western Hemisphere - Carrera-Martínez, Roberto; Snyder, Bruce A. (Zootaxa, 2016)
The earthworm fauna of North America is still greatly unknown, with undescribed native species and new records of invasive species continually being discovered. The most recent checklists are difficult to reconcile, since they vary in their geographic coverage and taxonomy. Reynolds & Wetzel (2012) state that North America (including all of Mexico, some of the Caribbean, and Hawaii) is home for 256 species of earthworms, from which 188 are considered native or endemic and 68 are peregrine, exotic, and invasive species. Blakemore (2008) listed North America north of Mexico as having 183 earthworm species, of which 59 species are exotic. One Megascolecidae genus, Amynthas, is mostly located in the warmer subtropical and tropical regions of the world, with a few species that are able to survive the winter in the temperate zones of North America (Edwards & Bohlen 1995; Görres et al. 2014). Here we report for the first time the occurrence of Amynthas carnosus (Goto & Hatai, 1899) in the United States. To our knowledge, this is not only the first report of A. carnosus in North America, but also its first report in the Western Hemisphere. The description below is intended to place our specimens in the correct taxon while avoiding future confusion with similar species, without making changes to the existing classification system.